(untitled) (Current Problems in Rail Vehicles, 2021)
The paper outlines the possibilities of using the JASTI (Hybrid III 50th Percentile Male Pedestrian) dummy to assess the effects of a pedestrian collision with the front end of a tram in the context of legislation under preparation. A description of the dummy and the variables that were monitored in the tests carried out in the current project is presented. Furthermore, the limitations of the applicability of the dummy and the relation to simulation models are mentioned.